Little layer. Big result? - Powell, Dan (Cranfield University, 2024)
3MT contribution to the Defence and Security Doctoral Symposium 2023
Keywords: DSDS23; Ceramic armour; interlayers; interfaces; wave propagation; ballistic impact; DSDS23 3MT